The Japanese : - Ozaki, Robert S. (Charles E. Tuttle Co., 1978)
This book examines avariety of topics, among them Japan's early encounters with the West. Japanese philosophies of government, law, and ethics, and the way that the smooth working of modern insittutions such as the bureaucarcy and the corporation is reliant upon a strong sense of gruop and human relationships. Specialists in Japanese history will find particularly illuminating the description of emperor worship and political nonresponsibility in the years before World War II.